2021
DOI: 10.1371/journal.pone.0259192
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an acute neurological outbreak in Eluru, India, 2020

Abstract: On 4th December 2020, a sudden outbreak, with neurological symptoms like seizures, loss of consciousness etc., was reported in a town from south India. By 3rd day about 400 people were involved. A multi disciplinary team from our institute visited the site to investigate the outbreak. Based on the case history and clinical examination of the patients, the team suspected a probable diagnosis of an acute pesticide, heavy metal and/or mycotoxin exposure for which, biological samples (blood, urine) were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Moreover, convulsions are relatively rare in organophosphate poisoning, which is characterized by excessive salivation, sweating, and pin point pupil, often with poor prognosis [16]. The latest report of the outbreak by the Indian Council of Medical Research that conducted detailed laboratory analyses reported "relatively" high concentrations of triazophos pesticide in municipal water of affected households; however, the source of contamination was not identified [17].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, convulsions are relatively rare in organophosphate poisoning, which is characterized by excessive salivation, sweating, and pin point pupil, often with poor prognosis [16]. The latest report of the outbreak by the Indian Council of Medical Research that conducted detailed laboratory analyses reported "relatively" high concentrations of triazophos pesticide in municipal water of affected households; however, the source of contamination was not identified [17].…”
Section: Discussionmentioning
confidence: 99%